Upaya Guru Pendidikan Agama Islam dalam Meningkatkan Motivasi Belajar Menghafal Al-Qur'an di SMP Al-Muslim Sidoarjo - Aslachah, Siti; Musawir, Musawir (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This research focuses on the efforts of Islamic Education teachers and the challenges they face in enhancing the motivation of students at SMP Al-Muslim Sidoarjo to memorize the Quran. This qualitative field research involves teachers and students at the school, utilizing data collection methods such as observation, interviews, and documentation. The gathered data will be presented in an easily understandable manner and then analyzed to draw conclusions. The research findings indicate several strategies employed by Islamic Education teachers to boost students' motivation in memorizing the Quran at SMP Al-Muslim Sidoarjo. These include providing positive motivation, assigning tasks and assessments, and guiding students in the muraja'ah process. However, there are challenges faced by the teachers, such as students' difficulties in reciting the Quran with tartil, a lack of discipline during the teaching and learning process, students' tendency to be lazy when memorizing the Quran, and variations in intelligence levels among students. Through an understanding of these efforts and challenges, this research contributes significantly to enhancing the effectiveness of teaching methods and student motivation in understanding and memorizing the Quran in the Islamic education environment of SMP Al-Muslim Sidoarjo.